An investigation of the survival level of Oreochromis mossambicus fry variably kept in a closed system : laboratory experiment - Asgodom, Mihretu T. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Animal Sciences. Aquaculture))--University of Stellenbosch, 2005.